Core excitation of some organometallic and organosilicon molecules - Wen, Alex T. (My University, 1992)
Inner-shell electron energy-loss spectroscopy (ISEELS) is an electron impact technique for the examination of inner-shell excitation of matter in the soft X-ray energy range between 20 and 1000 eV. It has long been utilized to study the core-excitation spectra of atoms and small organic or inorganic molecules. This thesis demonstrates the extension of such investigations to large organometallic complexes and organosilicon compounds in the gas phase. Measured under low momentum transfer conditions (>2.5 keV impact energy and small scattering angle, ≤2∙), where the spectra are dominated by electric-dipole-allowed transitions, ISEELS spectra have been recorded for transition metal carbonyls Fe(CO)₅, Fe₂(CO)₉ and CO₂(CO)x; metallocenes Fe(C₅H₅)₂, CH₂CH-C₅H₄FeC₅H₅, C₄H₉-C₅H₄FeC₅H₅ and Co(C₅H₅)₂; mixed-ligand complexes C₅H₅TiCl₃, C₆H₆Cr(CO)₃, organopolysilanes (CH₃)₃SiSi(CH₃)₃ and Si[Si(CH₃)₃]₄ as well as related compounds TiCl₄, C₅H₆ and (C₅H₆)₂. The spectral features have been assigned on the basis of comparison with the spectra of the free ligands and with a few previous studies of related organometallic/organosilicon species, along with extended Hückel molecular orbital calculations. The spectra provide novel insight into how inner-shell excitation spectroscopy reflects the metal-ligand bonding in these complexes and ligand-ligand interaction via the central metal atom. All the O 1s spectra are similar to each other, and the C 1s and metal 2p spectra of related compounds in a series (e.g., carbonyl complexes or metallocene derivatives) also have a similar shape, suggesting similar origins of the spectral features. Small variations through each series have been interpreted in terms of changes in the electronic structure associated with changing substituents. The metal 2p spectra are found to be surprisingly sensitive to the identity of the ligands present in the complexes and/or the character of the metal-ligand bonding. A resonance associated with the Si-Si σ* antibonding molecular orbital is identified at 102.5 eV in the Si 2p spectra of the two organosilicon compounds.
Keywords: Chemistry; Chemistry